MINAT PENGGUNAAN DIGITAL PAYMENT DI KALANGAN MILLENIAL TANJUNGPINANG - Afriyadi Afriyadi (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the interest in using digital payments for the millennial generation in Tanjungpinang City. This research was conducted quantitatively with the number of samples in this study as many as 80 respondents from the millennial generation of Tanjungpinang City. The analytical method used consists of data quality test, classical assumption test, hypothesis test, multiple linear regression and coefficient of determination. Data were analyzed using SPSS 21.00 for windows. The results of the study show that the perceived benefits of using digital transactions (X1), perceptions of the ease of using digital transactions (X2), Perceptions of Security Risks in Using Digital Transactions (X3) have a significant effect on interest in using digital transactions, interest in using digital payments among millennials in Tanjungpinang City. (Y) either partially or simultaneously, with the regression equation in this study is Y = 6.208 + 0.123 X1 + 0.270 X2 - 0.14 X3 + €. The results of the determination test (R2) show the Adjust R Square value of 0.866. This figure shows the magnitude of the influence of the independent variable on the dependent variable of 86.6% and while the remaining 3.34% is influenced by other variables not examined in this study.